Influence of diet nutrient density and a multicarbohydrase containing α-galactosidase on performance, carcass characteristics, breast myopathies, and nutrient utilization of broilers reared from 1 to 42 days of age - J.P. Gulizia; J.I. Vargas; S.M. Bonilla; J.R. Hernandez; L.M. Almeida; P. Soster; S. Thuekeaw; B. Hutson; S. Llamas-Moya; T. Duong; W.J. Pacheco (Poultry Science)
This study evaluated the effects of nutrient density and the usage of a multicarbohydrase containing α-galactosidase enzyme (CAG) on broiler performance, carcass characteristics, and nutrient utilization from 1 to 42 d of age. A total of 1,800 d-old YPM x Ross 708 male broilers were distributed randomly into 72 floor pens (25 birds/pen) and assigned to 1 of 6 treatments (12 replicates/treatment). Three basal diets were formulated with 2 ME levels (adequate (AE) and 100 kcal/kg reduced (RE)) and 2 amino acid (AA) densities (96 and 90%) following Ross 708 nutrient specifications. The first diet, AE96AA, contained AE and 96% AA density. The second diet, RE96AA, contained RE with 96% AA density. The third diet, RE90AA, contained RE with 90% AA density. Additional treatments were prepared by supplementing 0.2 g CAG per kg feed to the basal diets. Broiler performance (d 14, 28, and 42), processing yields (d 43), breast myopathies (d 43), apparent ileal nutrient digestibility (d 42), and digestible nutrient intake (d 29 to 42) were determined. Data were analyzed as a 3 × 2 (nutrient density x CAG) factorial arrangement of treatments. Nutrient density x CAG interactions were observed for multiple measurements including feed conversion ratio (FCR; d 1 to 42), CP digestibility, and apparent ileal digestible energy (AIDE). Day 1 to 42 FCR was reduced when broilers were fed RE90AA with CAG compared to RE90AA without CAG (P ≤ 0.05). Crude protein digestibility increased when broilers consumed AE96AA without CAG compared to RE90AA, whereas CAG inclusion allowed for similar CP digestibility between all nutrient densities (P ≤ 0.05). Without CAG inclusion, AIDE had a stepwise decrease from AE96AA to RE90AA, while CAG supplemented AE96AA and RE90AA had similar AIDE (P ≤ 0.05). Inclusion of CAG decreased FCR, and increased nutrient digestibility of broilers fed nutrient-reduced diets.